1985
DOI: 10.1007/bf01993441
|View full text |Cite
|
Sign up to set email alerts
|

Construction and preliminary evaluation of a simulation model of the population dynamics of the potato cystnematode Globodera pallida

Abstract: A model is constructed to simulate the popuiation dynamics of the potato cyst-nematode, Globodera pal/ida, and its effect on the growth of the potato. Parameters and rate variables are estimated from published data, and a preliminary evaluation is performed. Despite its simplicity, the model can provide realistic predictions of the real system's behaviour: the predicted relation between initial nematode density and the annual multiplication rate, and the effect of nematode density on tuber yield, are simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…The above results indicated that, on susceptible potato, the increase of a PCN field population is on average similar to that of other growing areas (Trudgill et al, 1987) and the annual multiplication rate with all initial densities is as described in Ward et al (1985). The average population density in the monoculture plots was a little less than the average (85 larvae g -' ) in the experiment reported by Jones & Parrott (1969).…”
Section: Discussionsupporting
confidence: 72%
“…The above results indicated that, on susceptible potato, the increase of a PCN field population is on average similar to that of other growing areas (Trudgill et al, 1987) and the annual multiplication rate with all initial densities is as described in Ward et al (1985). The average population density in the monoculture plots was a little less than the average (85 larvae g -' ) in the experiment reported by Jones & Parrott (1969).…”
Section: Discussionsupporting
confidence: 72%
“…These range from a straight line relation between yield and initial nematode population density (Brown, 1969), deterministic equations developed by Seinhorst (1965) and Elston, Phillips & Trudgill(1990), in which nematode population density is expressed on a log. scale, to the interactive model described by Ward, Rabbinge & den Ouden (1985). None of these models can be used t o predict satisfactorily yield losses without additional 0 1990 Association of Applied Biologists information on various environmental factors including soil type, the likely yield potential of the site and of the cultivar (Trudgill, 1986a).…”
Section: Introductionmentioning
confidence: 99%
“…Effective modelling of crop growth and yield losses due to PCN is also required to develop predictive models of PCN population dynamics (Ward et al, 1985). Several models have been described which are based on the observation that, in one season, the multiplication rate of PCN decreases with increasing initial population density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation